An Analysis of Islamic Religious Education Teachers’ Efforts In Enhancing Students’ Learning Interest in Fiqh at MTs Al-Amien - Yusli Yusli; Moh Hamdan Baihaqi (Jurnal Pendidikan Educandum, 2026)
This article was written with the aim of describing the efforts of Islamic Education teachers in building students' interest in learning Islamic jurisprudence at Mts Al-Amien. This research is motivated by the importance of enhancing students' interest in learning Fiqh, an integral part of Islamic Religious Education (PAI). Low learning interest can hinder the achievement of educational objectives, particularly in developing a profound understanding of religious teachings. Therefore, this study aims to examine the efforts of PAI teachers in increasing students' interest in learning Fiqh and analyze the supporting and inhibiting factors in the learning process at MTs Al-Amien Kota Kediri. The research employs a descriptive qualitative method with a field study approach. Data collection techniques include participatory observation, in-depth interviews with teachers and students, and analysis of relevant documents. The results indicate that PAI teachers play strategic roles as educators, motivators, and evaluators, which have proven effective in increasing students' learning interest. Supporting factors include students' high curiosity about Fiqh materials, while inhibiting factors consist of students' initial lack of interest and peer distractions.